FRI0333 Effects of Tofacitinib Treatment on Leptin and other Components of the Multi-Biomarker Disease Activity Score in Patients with Rheumatoid Arthritis. (10th June 2014) - Yamaoka, K.; Kubo, S.; Li, W.; Sonomoto, K.; Hirata, S.; Sasso, E.H.; Saito, K.; Defranoux, N.A.; Tanaka, Y.
Abstract : Background: The muti-biomarker disease activity (MBDA) score has been validated as an objective tool to assess disease activity in patients with rheumatoid arthritis (RA) (1). We have previously reported that MBDA score tracked clinical disease activity in patients with RA treated with tofacitinib. Objectives: To evaluate the relationships between the 12 component biomarkers of the MBDA score and the clinical features of patients with RA treated with tofacitinib. Methods: We studied 37 patients with RA who had been enrolled in Phase 2 or 3 clinical trials of tofacitinib at the University of Occupational and Health, Japan (UOEH). Patients had been randomized to receive different doses of tofacitinib (0-15 mg twice daily (BID)) for the first 3-6 months, as monotherapy (N=8) or with concomitant methotrexate (N=29); after 12-24 weeks, all patients were given 5 mg (N=25) or 10 mg (N=12) BID of tofacitinib. Serum concentrations of VCAM-1, EGF, VEGF-A, IL-6, TNF-RI, MMP-1, MMP-3, YKL-40, leptin, resistin, CRP, and SAA were measured at baseline and 1 year and used to calculate the MBDA score using the validated VECTRA® DA algorithm. DAS28-ESR and mTSS were measured at baseline and 1 year. Wilcoxon's signed rank test was used to assess the changes in biomarkers. Correlations between the changes in leptin and other variables were evaluated by Spearman's correlation (r). Results: Baseline patient characteristics (mean ± SD) were: age 55 (±12), disease duration 7 years (±7), DAS28-ESR 6.4 (±1.1), MBDA score 61 (±15), and mTSS 69 (±84). 84% were female, 86% were RF+, 24% received concomitant glucocorticoid and 78% concomitant MTX. DAS28-ESR and MBDA score decreased for nearly all patients; their mean values at 1 year were to 3.0 and 28 respectively. Except for leptin and EGF, serum concentrations of all biomarkers decreased significantly (p<0.05) from baseline to 1 year. Leptin concentration increased significantly from median 3.4 ng/ml to median 6.1 ng/ml (p<0.001). Median EGF concentration increased (from 121 pg/ml to 171 pg/ml) although not statistically significantly. Leptin levels increased in 29 patients (78%). Change (Δ) in leptin was inversely correlated with ΔMBDA (r= -0.35, p=0.034), ΔIL-6 (r= -0.32, p=0.052), and ΔCRP (r= -0.38, p=0.02) and positively with ΔEGF (r=0.38, p=0.021). There was no statistically significant correlation between Δleptin and ΔDAS28 or ACR response, and between leptin and MBDA scores at baseline or 1 year. Conclusions: Concentrations of most of the MBDA components significantly decreased in patients treated with tofacitinib. Exceptions were EGF, which tended to increase, and leptin, which increased statistically significantly. This observed increase in leptin differs from what has been reported for patients with RA treated with TNF inhibitors (2). While further study is needed to clarify the effect of tofacitinib on leptin, the MBDA score captured the overall effect of tofacitinib on disease activity. References: Curtis JR & al., Arthritis Care Res. 2012; 64(12):1794-803. Gonzalez-Gay MA & al., Clin Exp Rheumatol. 2009; 27(2):222-8. Disclosure of Interest: K. Yamaoka Consultant for: Pfizer Japan Inc., S. Kubo: None declared, W. Li Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, K. Sonomoto: None declared, S. Hirata: None declared, E. Sasso Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, K. Saito: None declared, N. Defranoux Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, Y. Tanaka Grant/research support: Bristol-Myers Squibb, MSD K.K., Chugai Pharma Co., Ltd., Mitsubishi-Tanabe Pharma Co., Ltd., Astellas Pharma Inc., Abbott Japan Co., Ltd., Eisai Co., Ltd. and Janssen Pharmaceutical K.K., Speakers bureau: Mitsubishi-Tanabe Pharma Co., Ltd., Abbott Japan Co., Ltd., Eisai Co., Ltd., Chugai Pharma Co., Ltd., Janssen Pharma K.K., Santen Pharma Co., Ltd., Pfizer Japan Inc., Astellas Pharma Inc., Daiichi-Sankyo Co., Ltd., GlaxoSmithKline K.K., Astra-Zeneca, Otsuka Pharma Co., Ltd., Actelion Pharma Japan Ltd., Eli Lilly Japan K.K., Nippon Kayaku Co., Ltd., UCB Japan Co., Ltd., Quintiles Transnational Japan Co. Ltd., Ono Pharma Co., Ltd. DOI: 10.1136/annrheumdis-2014-eular.2292